(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2017)
A novel, sensitive, specific, accurate and reproducible reverse phase high performance liquid chromatographic analytical method (RP-HPLC) was developed and validated for estimation of total benzalkonium chloride (BKC) content as a preservative in azelastine hydrochloride pharmaceutical ophthalmic formulation. The reversed phase HPLC method was used with C18, cosmosil (250 mm × 4.6mm i.d. × 5µm) column. The mobile phase was used as a combination of acetonitrile and buffer (adjusted to pH 5.0 with 5N NaOH) in the ratio of 45:55 % v/v, mobile phase was pumped at a constant flow rate of 1.5 ml per minute. The quantification of benzalkonium chloride was carried out with UV detection at 210 nm and column oven temperature was 25°C. By using these chromatographic conditions of method, four homologues of benzalkonium chloride were separated without any interference of any drug product components. The obtained results were found linear in concentration range 40µg/ml to 60µg/ml (50µg/ml ± 20%), correlation coefficient of calibration curve of regression data was 0.999 value. Recovery was found to be 99.0%, 100.4% and 101.1% at ± 30% of theoretical target concentration. The %RSD for method precision, instrument precision were found 0.26% and 0.10% respectively. The method has been statistically validated as per international council for harmonization guideline Q2R1 and found within the acceptance criteria. So that the method was found specific, linear, precise and accurate for quantification of total benzalkonium chloride content as a preservative in azelastine hydrochloride pharmaceutical ophthalmic formulation.